UPAH SULAM BIBIR DAN ALIS PERSPEKTIF HUKUM ISLAM - Moh. Sholehuddin (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
The research data were collected through the views of scholars of the act changing God's creation, the views of scholars associated with Qiya>s, Islamic views pertaining to ingredients halal and haram, and the views of medical experts to the effects of the lip and eyebrow embroidery. Then analyzed with descriptive analysis techniques. The study concluded that the lip and eyebrow embroidery is haraam for two reasons. First, lip and eyebrow embroidery is an act (ornate) excessively that this act hated God. As word of Allah in Surah al-A'raf paragraph 31: "Hi, Son of Adam, wear beautiful clothes in every (enter) mosque, eat and drink, and do not exaggerate. Allah loves not those who exaggerated. " While the result of doing israf described in God's word Surah al-Isra'paragraph 27: “Real, the wasters that are brothers of Satan and the devil it is ingrate to his Lord. "Second, the danger outweigh the benefits. The author uses the rules: "Rejecting the main danger is more than attaining goodness.